CITTASLOW SOM CITYBRAND – KAMPEN FOR AT GENVINDE DEN LOKALE HETEROGENITET - Larsen, Pernille (K&K - Kultur og Klasse, 2010)
CITTASLOW AS CITYBRAND – THE STRUGGLE OF REGAINING LOCAL HETEROGENEITY This article illustrates how city branding is the new “tool” to orchestrate the city to attract the attention of tourists, inhabitants and investors. The specific object of analysis in this article is Svendborg, which is a very interesting case because the town is the first in Denmark to brand itself as a Cittaslow. Today there are about 120 Cittaslows all over the world. The Cittaslow movement was founded in Italy in 1999, inspired by the “Slow Food” movement, which was also founded in Italy as a contrast to the fast-food culture and the increasing Americanisation of our society. Through this article I will describe and analyse the Cittaslow movement. In a wider cultural perspective, I will also illustrate the way in which we can understand the will to be a “slow city” as part of a new interesting discourse with “slowness” being valued as the new rationale in a global world which is growing increasingly fast and changeable. On the other hand, I will also discuss how we can understand the Cittaslow movement as a contrast to the increasingly mono-cultural world because the slow city tries to reclaim the importance of local identity and cultural plurality.